Understanding Frequency Dependence of Trap Generation Under AC Positive Bias Temperature Instability Stress in Si n-FinFETs - Yunfei Shi; Hao Chang; Hong Yang; Qiangzhu Zhang; Qianqian Liu; Bo Tang; Longda Zhou; Zhigang Ji; Junjie Li; Xiaobin He; Junfeng Li; Huaxiang Yin; et al. (IEEE Journal of the Electron Devices Society)
In this paper, the frequency (f) dependence of trap generation in Si n-channel fin field-effect transistors (n-FinFETs) under AC positive bias temperature instability (PBTI) stress is investigated by fast direct-current current-voltage (DCIV) method and the discharging-based multi-pulse energy profiling (DMP) technique. The experimental results show that both interface trap generation ( $Δ $ NIT) and bulk trap generation ( $Δ $ NOT) of n-FinFET under AC PBTI stress are almost independent of the AC frequency. However, further analysis shows that $Δ $ NOT consists of shallow traps near EC of Si and deep traps near Ev of Si. Moreover, about 22% of deep traps decrease with shallow traps increasing under 1.4V overdrive voltage (Vov) at 125°C with AC bias frequency increasing from 10 Hz to 1 MHz.